The impact of artificial intelligence on internal audit quality amidst the challenges of Algeria’s IT infrastructure - Merkhoufi, Mouloud; Bouzidi, Abderraouf; Sadani, Zobir (International journal of economic perspectives, 2024)
This research aims to evaluate the mutual impact of artificial intelligence (AI) and information technology infrastructure on the quality of audit processes in Algerian organizations. The study adopted a structural modeling approach using SmartPLS to analyze data collected from a sample of internal auditors, academicians in the field of auditing, and professionals working in Algeria. The findings revealed several key results. First, a robust IT infrastructure significantly contributes to improving audit quality by providing auditors with the necessary tools and data. Second, the study confirmed that AI offers substantial value to audit processes by automating routine tasks and analyzing large volumes of data with high accuracy. Furthermore, the results indicated that the impact of AI and infrastructure is complementary, as each enhances the other. The infrastructure provides a suitable environment for AI application, while AI, in turn, leverages this infrastructure to achieve better results. In conclusion, investing in developing the infrastructure and adopting AI technologies represents a strategic investment for Algerian organizations. This investment contributes to improving audit quality, enhancing trust in financial reports, and achieving greater efficiency and effectiveness in operations.